2022
DOI: 10.1186/s13063-022-06095-1
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of FRozen Encapsulated multi-donor Stool filtrate for active ulcerative Colitis (FRESCO): study protocol for a prospective, multicenter, double-blind, randomized, controlled trial

Abstract: Background Ulcerative colitis (UC) is a chronic inflammatory bowel disease with significant morbidity and mortality. Although the precise cause remains unknown, disturbances in the intestinal microbial community have been linked to its pathogenesis. Randomized controlled trials in UC and relapsing Clostridioides difficile infection (CDI) have established fecal microbiota (FM) transfer (FMT) as an effective therapy. In this context, preliminary results indicated that the transfer of sterile feca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In addition, the beneficial effects of FMT therapy have been related to the modulation of macrophage effector functions [ 27 , 28 ]. However, considering the limitations and challenges associated with FMT, the use of SFF is recently being recognized as an alternate approach for managing gut inflammatory disorders [ 14 , 29 ]. The present study thus evaluated whether SFF has the potency to stimulate as well as modulate macrophage functions that may be useful for maintaining cellular immune homeostasis and resisting inflammatory disorders respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the beneficial effects of FMT therapy have been related to the modulation of macrophage effector functions [ 27 , 28 ]. However, considering the limitations and challenges associated with FMT, the use of SFF is recently being recognized as an alternate approach for managing gut inflammatory disorders [ 14 , 29 ]. The present study thus evaluated whether SFF has the potency to stimulate as well as modulate macrophage functions that may be useful for maintaining cellular immune homeostasis and resisting inflammatory disorders respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Another technique fecal filtrate transplantation instead removes intact bacteria and only transfers bacterial debris, metabolites, and oligonucleotides [ 58 ]. It has been utilized successfully in CDI and is also being evaluated in UC in a clinical trial [ 59 ].…”
Section: Procedure-related Factors and Outcome Determinants In Fmtmentioning
confidence: 99%
“…58 It has been utilized successfully in CDI and is also being evaluated in UC in a clinical trial. 59…”
Section: Washed Fmt and Fecal Filtrate Transplantationmentioning
confidence: 99%
“…Interestingly, it was shown that sterile stool filtrate also eliminated symptoms in chronic Clostridioides difficile infection [48]. The ongoing FRESCO trial currently addresses the question of whether transfer of sterile stool filtrate may also be sufficient to treat UC [49]. However, FMT as a therapeutic option for UC should be reserved for well-controlled clinical trials until more evidence on its efficacy and safety will be available.…”
Section: List Of Abbreviationsmentioning
confidence: 99%